Multiple-Description Multistage Vector Quantization. (3rd December 2007) - Yahampath, Pradeepa
Abstract : Multistage vector quantization (MSVQ) is a technique for low complexity implementation of high-dimensional quantizers, which has found applications within speech, audio, and image coding. In this paper, a multiple-description MSVQ (MD-MSVQ) targeted for communication over packet-loss channels is proposed and investigated. An MD-MSVQ can be viewed as a generalization of a previously reported interleaving-based transmission scheme for multistage quantizers. An algorithm for optimizing the codebooks of an MD-MSVQ for a given packet-loss probability is suggested, and a practical example involving quantization of speech line spectral frequency (LSF) vectors is presented to demonstrate the potential advantage of MD-MSVQ over interleaving-based MSVQ as well as traditional MSVQ based on error concealment at the receiver.